Modelagem de um ambiente para análise de DNA em genética forense - Sarmento, Felipe José de Queiroz (2006)
The advances in molecular biology have increased the production of enormous amount of genetic information in a small period of time. This capacity of data production motivated the researchers to increase the rhythm of their researches. This necessity demands the use of efficient softwares in order to manage these data. Besides this, it also demands the development of good softwares in order to assist the researchers in the task of analyzing the data and giving them a biological meaning in a brief space of time. This work proposes a software model that will support the study of Forensic DNA, whose main repository is the autossomic DNA. This software intends to support the researchers in the identification of condemned persons or persons that are suspected of a crime. It also intends to assist the researchers in the study of paternity and the search for disappeared persons. The results of this work will be applied in the Forensic DNA Laboratory of UFAL. The software modeled here has four modules study of paternity , criminal , disappeared people and the bank of populational frequencies . The modules were modeled independently from each other, considering the specifications related to the analysis of genetic links. The software was developed using the JAVA programming language together with PostgreSQL database. Both are free software and have an excellent relationship between cost and benefit usage